Mechanistic insights into mode of action of rice allene oxide synthase on hydroxyperoxides: An intermediate step in herbivory-induced jasmonate pathway. (October 2016) - Tyagi, Chetna; Singh, Archana; Singh, Indrakant Kumar
Graphical abstract: Highlights: Allene Oxide Synthase of Oryza sativa sb. Japonica, interacts with 9- and 13- hydroxyperoxides. Phe347 and Phe92, the key residues, were mutated with Leucine and docked. Phe347 is more crucial for AOS functionality than Phe92 and is the differentiation factor between AOS and HPL pathway. Leu363 takes part in hydroxyperoxide catalysis instead of Phenylalanine in HPL. One Asn278 residue is also important for stability of the complexes in AOS and HPL. Abstract: Various types of oxygenated fatty acids termed 'oxylipins' are involved in plant response to herbivory. Oxylipins like jasmonic acid (JA) and green leafy volatiles (GLVs) are formed by the action of enzymes like allene oxide synthase (AOS) and hydroxyperoxide lyase (HPL) respectively. In this study, we focus on AOS of Oryza sativa sb. Japonica, that interact with 9- and 13- hydroxyperoxides to produce intermediates of jasmonate pathway and compare it with rice HPL that yields GLVs. We attempt to elucidate the interaction pattern by computational docking protocols keeping the Arabidopsis AOS system as the reference model system. Both 9-hydroxyperoxide and 13-hydroxyperoxide fit into the active site of AOS completely with Phe347, Phe92, Ile463, Val345, and Asn278 being the common interacting residues. Phe347 and Phe92 were mutated with Leucine and docked again with the hydroxyperoxides. The Phe347 → Leu347 mutant showed a different mode of action than AOS-hydroxyperoxide complex with Trp413 in direct bonding with the OOH group of 9-hydroxyperoxide. The loss of Lys88-OOH interaction in 13-hydroxyperoxide and loss-of-interaction of Leu347 indicated the importance of Phe347 residue in hydroxyperoxide catalysis. The second mutant Phe92 → Leu92 also shows a very different interaction pattern with 13-hydroxyperoxide but not with 9-hydroxyperoxide.Therefore, it can be concluded that Phe347 is more crucial for AOS functionality than Phe92. The aromatic ring of a Phenylalanine residue is important for catalysis and its mutation affects the binding of the two ligands. Another important residue is Asn278 which is an important part of the AOS catalytic site for maintaining stability and can be compared with the Arabidopsis AOS residue Asn321. Lastly, the interaction of HPL with these two derivatives involves Leu363 residue instead of Phe347 and thus, validating the importance of Phe → Leu substitution to be the reason of different modes of action that result in completely different products from same substrates.